2018
DOI: 10.1007/s00406-018-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

Brief vs. ultrabrief pulse ECT: focus on seizure quality

Abstract: The effect of electroconvulsive therapy (ECT) performed with ultrabrief pulse (UBP) stimulation has been found inferior to brief pulse (BP) ECT in various studies. We reinvestigated this issue using a new dosing strategy that is based on seizure quality instead of seizure threshold. There is a long history of studies associating ictal characteristics of ECT with the clinical outcome. Accordingly, we used the clinical status of the patient and the quality of the prior seizure to determine the dosage for the upc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Importantly, the point at which a ceiling effect is reached may vary between treatment techniques, with the results of Galvez et al, 2017 (where ultra-brief right unilateral ECT was delivered at 6e8 times seizure threshold) suggesting that changes in seizure intensity for ultra-brief right unilateral ECT can be seen at higher doses above threshold than for brief pulse right unilateral ECT [53]. This would also seem to be broadly consistent with the findings of Brunner et al, 2018, suggesting comparable ictal seizure quality can be produced with brief pulse and ultra-brief pulse right unilateral ECT, provided sufficient suprathreshold dosing is used for ultrabrief treatments [45]. Conversely, the ceiling for bilateral stimulation may be even lower than for right unilateral brief pulse ECT, though this has not been specifically tested (with obvious restriction on the degree to which stimulus intensity has exceeded seizure threshold in studies examined).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Importantly, the point at which a ceiling effect is reached may vary between treatment techniques, with the results of Galvez et al, 2017 (where ultra-brief right unilateral ECT was delivered at 6e8 times seizure threshold) suggesting that changes in seizure intensity for ultra-brief right unilateral ECT can be seen at higher doses above threshold than for brief pulse right unilateral ECT [53]. This would also seem to be broadly consistent with the findings of Brunner et al, 2018, suggesting comparable ictal seizure quality can be produced with brief pulse and ultra-brief pulse right unilateral ECT, provided sufficient suprathreshold dosing is used for ultrabrief treatments [45]. Conversely, the ceiling for bilateral stimulation may be even lower than for right unilateral brief pulse ECT, though this has not been specifically tested (with obvious restriction on the degree to which stimulus intensity has exceeded seizure threshold in studies examined).…”
Section: Discussionsupporting
confidence: 73%
“…The authors noted the limited sample size (25 patients) and need for replication as caveats to interpretation of these results. More recently, Brunner & Grozinger (2018) performed a retrospective evaluation of brief pulse and ultra-brief pulse treatments from a clinical service in which stimulus intensity was determined from the quality of the prior seizure and the clinical status of the patient throughout the treatment course [45]. As hypothesised, ultra-brief ECT seizures were comparable with brief pulse seizures on measures of ictal quality (and produced similar clinical outcomes), however those receiving ultra-brief ECT required higher charges, more dose increases during a course and more switches to bilateral ECT in this service.…”
Section: Impact Of Treatment Technique E Pulse Widthmentioning
confidence: 99%
“…It has been suggested that there might be a continuum of increasing efficacy (and adverse effects) with increasing pulse width (95), but how to change parameter settings in order to increase the stimulus dose has not been fully studied (105). In practice, EEG parameters (e.g., duration, amplitude, postictal suppression) are used as markers of seizure adequacy and guides to adjustment (i.e., increase) of the stimulus dose at subsequent treatments (106)(107)(108)(109).…”
Section: Techniquementioning
confidence: 99%
“…Threshold increases over a treatment course were detected by percentage change in midictal amplitude and potentially by postictal suppression [27]. In addition, a stimulation strategy (Clinical and Seizure Based Stimulation) based on seizure quality instead of seizure threshold that adapts the stimulus intensity according to the clinical status of the patient and the quality of the prior seizure has been successfully used [28].…”
Section: Introductionmentioning
confidence: 99%